Impacts of Climate Smart Agriculture Practices on Soil Water Conservation and Maize Productivity in Rainfed Cropping Systems of Uganda - Zizinga, Alex; Mwanjalolo, Jackson-Gilbert Majaliwa; Tietjen, Britta; Bedadi, Bobe; Gabiri, Geofrey; Luswata, Kizza Charles (Frontiers in Sustainable Food Systems, 2022)
With climate change, maize production is becoming more constrained by limited water availability especially in rainfed production systems. Climate Smart Agriculture (CSA) practices have potential to enhance water availability and water use efficiency in rainfed production systems, but their efficiencies have not been adequately investigated. The study evaluated the performance of permanent planting basins (PPB), mulching (M), and halfmoon pits (HM) on soil moisture storage, maize yield, and water use efficiency in a maize cropping system for the sub-humid areas of Uganda for three cropping seasons in Albert region. The control treatment consisted of bare soil as the existing conventional farming practice without any CSA practice. Maize growth parameters and soil moisture storage were monitored and evaluated in each cropping season and CSA treatment. The maize yield, water use efficiency, and evapotranspiration (ET), were determined in each CSA treatment. Results showed that CSA practices significantly increased (P < 0.05) total soil water storage (1–12%) than the control treatment. It was also noted that; the use of M, PPB, and HM increased the water use efficiency by 9 – 68% and 8 – 66% of grain yield compared to the control in the three growing seasons. Our results indicate that even under unreliable and limited precipitation in sub-humid regions, the studied CSA practices indicate a high possibility to increase maize productivity than conventional farming practices (control). These findings are critical as climate change continues to affect maize productivity in rainfed farming systems where there limited supplemental water alternative sources for smallholder farmers. The adoption of CSA practices will enhance the resilience of maize production in sub-humid regions.